Handbuch Europäische Sprachkritik Online (Handbuch Europäische Sprachkritik Online, 2018)
This second volume of the “Online Handbook of Language Criticism – A European Perspective” focuses on the processes of standardisation in German, English, French, Italian, and Croatian and investigates them in the context of language criticism, comparing different aspects of standardisation and authorities involved. It highlights diachronic aspects relating to the shaping of norms for written and spoken language as well as synchronic aspects, such as the development of pluricentric standards and issues of orthography and codification. In dem vorliegenden Handbuchband werden aus sprachkritischer Sicht Standardisierungsprozesse im Deutschen, Englischen, Französischen, Italienischen und Kroatischen behandelt sowie Instanzen und Bereiche der Standardisierung verglichen. Hierbei geht es sowohl um Aspekte der Diachronie, welche die Herausbildung von Normen für die geschriebene und gesprochene Sprache betreffen, als auch um synchrone Gesichtspunkte wie aktuelle plurizentrische Normtendenzen, Fragen der Orthographie und der Kodifizierung.